The Impact of Authoritarian Regimes on Families … and on Therapists1. Issue 3 (22nd October 2017) - Sluzki, Carlos E.
Abstract : Repressive powers require not only obedience on the part of the oppressed but also denial of the oppressive nature of their submission. While authoritarian governments are the focus of this article, this applies to any oppressive relationship. There is a slippery slope from experiencing the imposed nature of the oppressive rules to adapting to them to denying both internal and external evidence of their existence. To prevent that declining process becomes an urgent priority when totalitarianism appears on the political and interpersonal horizon, as it is to help people coming out of tyranny – therapists included – to recover the words and the agency lost in their previous experiences.